Behavioral and social competency profiles of stutterers - Giorgetti, Marília de Paula [UNESP] (2015)
Purpose: To investigate the behavioral and social competency profiles of individuals who stutter and to compare them with persons who do not stutter, according to their parents; to correlate the behavioral and the social competence performances with the severity of stuttering. Methods: Sixty-four participants, aged 6 to 18 years, of both genders, were divided into two groups: the study group (SG), composed of 32 individuals with persistent developmental stuttering, and the control group (CG), composed of 32 fluent individuals. The procedures used were fluency assessment, stuttering severity instrument, and the Child Behavior Checklist inventory. Results: In the behavioral profile of the SG, the mean of the total score and that of the internalizing problems were classified as clinical. The comparison between the groups showed differences in the behavioral profile concerning the total score, and in the internalizing and externalizing problems; and in the social profile, concerning the total score and activity scale. There were no statistically significant differences in the scales among the mild, moderate, and severe stuttering. Conclusion: According to the information provided by parents, children who stutter showed peculiar behavior and social competence, with a higher tendency to manifest alterations in this area, in comparison to those who do not stutter. Fear, nervousness/tension, guilt, anxiety, perfectionism, and worry were the most frequent alterations in relation to the behavior, whereas damages in the social field and in the habitual communication situations characterized the social competence of persons who stutter.